Queryable Provenance Metadata For GDPR Compliance - O'Sullivan, Declan; Lewis, David (My University, 2018)
Information associated with regulatory compliance is often siloed as legal documentation that is not suitable for querying or reuse. Utilising open standards and technologies to represent and query this information can facilitate interoperability between stakeholders and assist in the task of maintaining as well as demonstrating compliance. In this paper, we show how semantic web technologies can assist in representation and querying of compliance information related to the General Data Protection Regulation (GDPR), an European law governing the use of consent and personal data. We focus on the subset of obligations related to the use of consent and personal data, and represent the associated metadata using the previously published GDPRov ontology and GDPRtEXT resource. We present a proof-of-concept demonstration (available online) where information is queried to automatically populate the GDPR-readiness checklist published by Ireland’s Data Protection Commissioner.
Procedia Computer Science
SEMANTICS 2018
PUBLISHED
Vienna, Austria
Keywords: General Data Protection Regulation (GDPR); General Data Protection Regulation (GDPR); Digital Engagement; Knowledge and data engineering